Wiring the writing center - Hobson, Eric (Utah State University Press, 1998)
As computers have brought important developments to composition studies, writing centers have found themselves creating and improvising applications for their own work and often for the writing programs and institutions in which they live. Online tutorials, websites with an array of downloadable resources for students, scheduling and email possibilities--all of these are becoming common-place among writing centers across the country. However, in spite of impressive work by individual centers, exchange on these topics between and among writing centers has been sporadic. As more writing centers.
Keywords: English language -- Rhetoric -- Study and teaching -- Data processing.; Report writing -- Study and teaching -- Data processing.; English language -- Computer-assisted instruction.; Report writing -- Computer-assisted instruction.; Writing centers -- Automation.; Rapports -- Rédaction -- Étude et enseignement -- Informatique.; Rapports -- Rédaction -- Enseignement assisté par ordinateur.; Centres de communication écrite -- Automatisation.; LANGUAGE ARTS & DISCIPLINES -- Rhetoric.; REFERENCE -- Writing Skills.; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing.; English language -- Computer-assisted instruction; English language -- Rhetoric -- Study and teaching -- Data processing; Report writing -- Computer-assisted instruction; Report writing -- Study and teaching -- Data processing; Writing centers -- Automation; Electronic book.